EBSD investigation and magnetic properties of manganese ferrite crystallized in a sodium-silicate glass. Issue 30 (6th July 2018) - Harizanova, R.; Avramova, I.; Wisniewski, W.; Avdeev, G.; Tzankov, D.; Georgieva, M.; Gugov, I.; Rüssel, C.
Abstract : SEM micrograph with the IPF + IQ-maps of the polygon and dendritic MnFe2 O4 crystals and an EBSD pattern acquired from a large jacobsite crystal. Abstract : Glasses were prepared in the system (100 − x )(0.16Na2 O/0.10MnO/0.74SiO2 )/ x Fe2 O3 ( x = 15 and 25 in mol%) by the traditional melt-quenching technique. Some of them were subsequently crystallized at temperatures in the range from 520 to 700 °C for times from 10 min to 100 h. The valence states of Fe and Mn in selected glasses and glass-ceramics were investigated by X-ray photoelectron spectroscopy (XPS) and showed the presence mostly of Mn 2+ while Fe occurs as both Fe 2+ and Fe 3+ . X-ray diffraction (XRD) analyses of the 15 mol% Fe2 O3 samples revealed that at lower temperatures and for short heat treatment times a solid solution with a spinel structure and a chemical composition between MnFe2 O4 (jacobsite) and Fe3 O4 (magnetite) crystallizes, while aegirine (NaFe(SiO3 )2 ) additionally occurs at higher temperatures and for longer annealing times. Here the average crystallite size of the jacobsite-based phase varies between 4 and 10 nm, as determined by XRD. The XRD analysis of the 25 mol% Fe2 O3 samples which spontaneously crystallize when quenching the melt only show the precipitation of the jacobsite–magnetite solid solution. The microstructure was investigated by scanning and transmission electron microscopy (SEM and TEM) as well as electron-backscatter diffraction (EBSD). The EBSD analyses show that the cubic crystals grow via the polygon as well as the dendritic growth mechanisms. The individual grains show independent orientations and inclusions of residual glass while a global crystallographic texture could not be detected. The obtained magnetization curves of the 25 mol% Fe2 O3 samples show hysteresis and a Curie temperature of approximately 480 °C which supports the XRD results. The samples with 15 mol% Fe2 O3 crystallized at 650 and 700 °C exhibit superparamagnetic behaviour and thin S-shaped magnetization curves with zero coercivity.